2D and 3D finite element comparative analysis of compressive properties of porous titanium - LI Yuhua; HE Yuxin; ZHANG Qian; ZHAO Rong; WANG Haojie; CHU Jinghui; NIU Libin (Fenmo yejin jishu)
In order to investigate the effect of pore structure on the compression properties of porous titanium, the compression process of porous titanium was simulated by finite element method. The influence of different pore structure parameters such as porosity, pore size and pore shape on the compression performance of porous titanium was studied. Meanwhile, the 2D and 3D finite element simulation results were compared and analyzed. The results show that elastic modulus and yield strength of porous titanium decrease with the increase of porosity, and the pore size has little effect on the compression properties. Among the three kinds of pore shapes, round hole has the best compression performance. For elliptical hole, the compression performance decreases with the decrease of the size of the hole in the compression direction. The 2D and 3D finite element simulation results are in agreement with Gibson-Ashby model and Nielsen model, and are closer to the experimental results. Both 2D and 3D finite element simulation results can accurately reflect the effect of pore structure on the compression properties of porous titanium, while the calculation time of 2D compression model is shorter.